2021
DOI: 10.3389/ftox.2021.639820
|View full text |Cite
|
Sign up to set email alerts
|

Adult Male Rats Show Resilience to Adolescent Bisphenol A Effects on Hormonal and Behavioral Responses While Co-Exposure With Hop Extracts Supports Synergistic Actions

Abstract: The adolescence period, marked by sexual and brain maturation, has shown sensitivity to various environmental disruptors. Exposure to the xenoestrogen bisphenol A (BPA) is known to alter physiological and behavioral responses although its role at this critical period remains largely unknown. Recent research further suggests biochemical and genomic effects of BPA to be mitigated by various natural compounds, while effects on behavior have not been examined. This study aimed to characterize (1) the effects of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…A BPA dose of 40 mg/kg/d was used in our study. Tis dose was selected from recently published studies that used a BPA dose of 40 mg/kg/d [36,37]. Te current study demonstrated signifcant histopathological and immunohistochemical changes in the coronary arteries and the hearts of the rats.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A BPA dose of 40 mg/kg/d was used in our study. Tis dose was selected from recently published studies that used a BPA dose of 40 mg/kg/d [36,37]. Te current study demonstrated signifcant histopathological and immunohistochemical changes in the coronary arteries and the hearts of the rats.…”
Section: Discussionmentioning
confidence: 97%
“…A BPA dose of 40 mg/kg/d was used in our study. This dose was selected from recently published studies that used a BPA dose of 40 mg/kg/d [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%